Design and Testing of a Milliampere Scale Leakage Current Sensor Based on a Current Transformer for Substation Lightning Protection - Gamma Aditya Rahardi; Hendra Dharma Putra; Dodi Setiabudi; Widyono Hadi; Arizal Mujibtamala; Dani Hari Tunggal Prasetiyo (Universitas Panca Marga, 2026)
Leakage current in lightning arresters is an important indicator of insulation conditions and protection system performance in substations, so a measurement method capable of detecting currents in milliamperes accurately and stably is required. This study aims to design and test a milliamperes-scale leakage current sensor that can be used for lightning arrester monitoring. The developed sensor is based on a current transformer with an analog signal amplification and filtering circuit, and data acquisition using a microcontroller. Testing was carried out experimentally by varying the resistive load and the number of turns, then the measurement results were compared with an AVO meter as a reference measuring instrument. The test results showed that the sensor was able to measure leakage current with a relatively low error rate, where the lowest error occurred at a load of 33 Ω and increased at larger loads due to a decrease in current. The relationship between current and load variation showed a linear characteristic with a coefficient of determination (R²) value close to 1. In addition, magnetic field analysis showed that the relative permeability value of the ferrite core was in the range of 88.4 to 98, which reflects the stability of the core's magnetic properties under various test conditions. Based on these results, the developed sensor has the potential to be used as part of a lightning arrester leakage current monitoring system to support the maintenance and reliability of the substation protection system.